Customer experience through online reviews from TripAdvisor: The case of Orlando theme parks - Costa, S. M.; Moro, S.; Rita, P.; Alturas, B. (International Journal of Technology Marketing, 2023)
In the last years, the development of social media and digital technology has empowered customers to strongly engage with firms, to freely behave choice wisely and to influence other customers either positively or negatively. This study sought to extract latent information on theme park visitor perception and experience through sentiment analysis from user generated content. In general, satisfaction and sentiment differed between the eight theme parks, wherein the three theme parks with higher positive sentiment were Disney's Animal Kingdom, followed by Universal's Islands of Adventures, Discovery Cove and finally SeaWorld. Furthermore, it was found on the one hand that drivers of customer's satisfaction were associated with sentiments such as 'fun', 'great', 'lovely' and 'amazing', and on the other hand experience and services like 'rides', 'water', 'dolphins', 'experience' and 'show'. Those results are valuable to support theme park management to improve guest experiences and consequently achieve sustainable competitive advantage.